It’s Complicated: Using Facebook to Create Emotional Connections in Student-Professor Relationships - Anthony Atkins (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
How can we use Facebook and other technologies to create emotional and professional connections with students?